Analisis Rantai Pasokan Komoditas Durian di Kecamatan Bolano Lambunu, Kabupaten Parigi Moutong - Nisa, Salma; Zainuddin, Fatlina; Syamsuddin, Syamsuddin; Hadi, Suryadi (Jurnal Samudra Ekonomi dan Bisnis, 2026)
This qualitative research focuses on the parties involved in the supply chain, commodity distribution flows, and obstacles encountered in the durian distribution process. Data were obtained through in-depth interviews, field observations, and documentation studies. The results show that the durian supply chain in Bolano Lambunu District involves farmers, collectors, wholesalers, processing factories/exporters, and end consumers, with distribution patterns still relying on traditional systems. Supply chain analysis on this site indicates a distribution system without the involvement of middlemen, allowing wholesalers to provide greater profits to farmers. Improving seed quality, promoting marketing, and strengthening distribution networks are key to developing a more sustainable supply chain. Support from the government and relevant institutions is also needed to improve infrastructure and market access, so that farmers can continue to improve their welfare in durian cultivation.